2023
DOI: 10.3389/fnhum.2023.1154798
|View full text |Cite
|
Sign up to set email alerts
|

Brain network mechanism on cognitive control task in the elderly with brain aging: A functional near infrared spectroscopy study

Abstract: ObjectiveTo study the brain network mechanism of cognitive control in the elderly with brain aging.Materials and methods21 normal young people and 20 elderly people were included in this study. Mini-mental State Examination and functional near-infrared spectroscopy (fNIRS) synchronous judgment test (including forward tests and reverse judgment tests) were performed on all subjects. To observe and compare differences in brain region activation and brain functional connectivity between subjects and forward and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
(41 reference statements)
0
0
0
Order By: Relevance
“…In FC studies fNIRS has been used successfully to confirm the finding of increased brain region co-operation, assumed to be due to brain's adaptation to the structural changes. [8] Furthermore, Nguyen et al found evidence of age-related decreased FC detected during verbal fluency task, although evidence of age-related changes during oddball and resting state was not found. [9] Arterial stiffness has been associated with aging and is one of the leading risk factors for hypertension [10].…”
Section: Introductionmentioning
confidence: 99%
“…In FC studies fNIRS has been used successfully to confirm the finding of increased brain region co-operation, assumed to be due to brain's adaptation to the structural changes. [8] Furthermore, Nguyen et al found evidence of age-related decreased FC detected during verbal fluency task, although evidence of age-related changes during oddball and resting state was not found. [9] Arterial stiffness has been associated with aging and is one of the leading risk factors for hypertension [10].…”
Section: Introductionmentioning
confidence: 99%